OP0085 Therapeutic Inhibition of Anti-Apoptotic BCL-2 Family Proteins in a Murine Model of Lupus Nephritis. (23rd January 2014) - Wang, L. C.; Perper, S.; Perron, D.; Tarcsa, E.; Bardwell, P.; Mozaffarian, N.; Souers, A.; Elmore, S.; Ghayur, T.; Olson, L.
Abstract : Background: Apoptosis is both a conserved and highly regulated process that is essential for normal development and tissue homeostasis. This process, also known as programmed cell death, is tightly regulated by the BCL-2 family proteins. Dysregulation of these proteins has been linked to survival of autoreactive lymphocytes and to Systemic Lupus Erythematosus (SLE). Inhibition of BCL-2 proteins may therefore ameliorate autoimmunity. Objectives: To determine the effect of inhibition of BCL-2 survival proteins in a murine model of lupus nephritis, as well as the effect on human leukocytes ex vivo. Methods: We have established previously that adenovirus vector-mediated delivery of murine IFN-α in lupus-prone (NZB × NZW)F1 mice induces a rapid and severe disease with many characteristics of SLE, including death due to severe glomerulonephritis. These mice were treated daily with vehicle or 3, 10, 30 mg/kg of navitoclax, a BH3 mimetic that binds with high affinity to BCL-2, BCL-XL, and BCL-W. Mycophenolate (100 mg/kg) was used as a clinical benchmark and positive treatment control. Proteinuria and survival data were presented as Kaplan-Meyer survival curves using Prism. For ex vivo human lymphocyte studies, B and T cells from healthy donors were cultured and treated with navitoclax overnight, prior to flow cytometric analysis. Some cultures were incubated with anti-CD40L/IgM or anti-CD3/CD28 to stimulate B or T cells, respectively. IC50 calculations were performed using Prism software (GraphPad). Results were considered significant at the level of p < 0.05. Results: BCL-2 family inhibition by navitoclax in the IFNa-induced (NZB x NZW) F1 lupus model significantly reduced both the incidence of severe proteinuria (≥ 300mg/dL) and mortality in a dose-dependent fashion as compared to vehicle controls ( p < 0.05). In addition, chronic administration of navitoclax at 30 mg/kg demonstrated 95% survival rate and 50% of animals without proteinuria as compared to 80% and 20%, respectively, in mycophenolate-treated animals. Consistent with its mechanism of action, navitoclax caused a dose-dependent reduction in murine lymphocyte counts, which correlated with long-term efficacy. In ex vivo human cell cultures, navitoclax treatment led to a rapid reduction in the numbers of both stimulated and unstimulated human lymphocytes, with B cells showing a higher sensitivity to navitoclax compared to T cells. Conclusions: Treatment of lupus nephritis-prone mice with the BCL-2 family inhibitor navitoclax resulted in significantly higher numbers of animals with preservation of renal function and overall survival. Furthermore, BCL-2 inhibition in ex vivo human lymphocyte cultures led to a rapid and selective reduction of B and T cells via apoptosis. Taken together, these data support a role for BCL-2 inhibition in the treatment of autoimmune diseases such as SLE. Disclosure of Interest: L. C. Wang Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center, S. Perper Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center, D. Perron Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center, E. Tarcsa Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center, P. Bardwell Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center, N. Mozaffarian Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., A. Souers Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., S. Elmore Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., T. Ghayur Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center, L. Olson Shareholder of: AbbVie Bioresearch Center, Employee of: AbbVie Bioresearch Center